Autoantibodies against the N-Methyl-d-Aspartate Receptor Subunit NR1: Untangling Apparent Inconsistencies for Clinical Practice - Ehrenreich, Hannelore (Frontiers in Immunology, 2017)
This viewpoint review provides an integrative picture of seemingly contradictory work published on N-methyl-D-aspartate receptor1 (NMDAR1) autoantibodies (AB). Based on the present state-of-knowledge, it gives recommendations for the clinical decision process regarding immunosuppressive treatment. Brain antigen-directed AB in general and NMDAR1-AB in particular belong to a preexisting autoimmune repertoire of mammals including humans. Specific autoimmune-reactive B cells may get repeatedly boosted by various potential stimulants (e.g. microbiome, infections, or neoplasms) plus less efficiently suppressed over lifespan (gradual loss of tolerance), likely explaining the increasing seroprevalence upon aging (>20% NMDAR1-AB in 80 year-old humans). Pathophysiological significance emerges (I) when AB specific plasma cells settle in the brain and produce large amounts of brain antigen-directed AB intrathecally, and/or (II) in conditions of compromised blood-brain-barrier (BBB), for instance upon injury, infection, inflammation or genetic predisposition (APOE4 haplotype), which then allows substantial access of circulating AB to the brain. Regarding NMDAR1-AB, functional effects on neurons in vitro and elicitation of brain symptoms in vivo have been demonstrated for immunoglobulin (Ig) classes IgM, IgA, and IgG. Under conditions of brain inflammation, intrathecal production and class switch to IgG may provoke high NMDAR1-AB (and other brain antigen-directed AB) levels in cerebrospinal fluid (CSF) and serum, causing the severe syndrome named ‘anti-NMDAR encephalitis’, which then requires immunosuppressive therapy on top of the causal encephalitis treatment (if available). However, negative CSF NMDAR1-AB results cannot exclude chronic effects of serum NMDAR1-AB on the central nervous system, since the brain acts as ‘immunoprecipitator’, particularly in situations of compromised BBB. In any case of suspected symptomatic consequences of circulating AB directed against brain antigens, leakiness of the BBB should be evaluated by CSF analysis (albumin quotient) and magnetic resonance imaging before considering immunosuppression.